2020
DOI: 10.3390/md18050262
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of the Marine-Derived Polysaccharides Laminarin and Chitosan on Aspects of Colonic Health in Pigs Challenged with Dextran Sodium Sulphate

Abstract: This study examined the effects of dietary supplementation with laminarin or chitosan on colonic health in pigs challenged with dextran sodium sulphate (DSS). Weaned pigs were assigned to: (1) a basal diet (n = 22); (2) a basal diet + laminarin (n = 10); and (3) a basal diet + chitosan (n = 10). On d35, the basal group was split, creating four groups: (1) the basal diet (control); (2) the basal diet + DSS; (3) the basal diet + laminarin + DSS; and (4) the basal diet + chitosan + DSS. From d39–42, the pigs were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 80 publications
0
15
0
Order By: Relevance
“…Bacteroids and Escherichia are highly related to gut inflammation, which are reported in several IBD animal models and patients of various literature (Yeom et al 2016 ; Rattigan et al 2020 ). Lactobacillus , as a kind of probiotic, exhibited beneficial effects on IBD by stimulating immune cells (Liu et al 2018 ).…”
Section: Discussionmentioning
confidence: 92%
“…Bacteroids and Escherichia are highly related to gut inflammation, which are reported in several IBD animal models and patients of various literature (Yeom et al 2016 ; Rattigan et al 2020 ). Lactobacillus , as a kind of probiotic, exhibited beneficial effects on IBD by stimulating immune cells (Liu et al 2018 ).…”
Section: Discussionmentioning
confidence: 92%
“…Bacteroids and Escherichia are highly related to gut in ammation, which are reported in several IBD animal models and patients of various literature (Yeom et al 2016;Rattigan et al 2020). Lactobacillus, as a kind of probiotic, exhibited bene cial effects on IBD by stimulating immune cells (Liu et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Rattigan R analyzed the role of chitosan or laminarin supplementation in the diet in the colonic health of DSSexposed pigs and reported that relative to the baseline DSS group, the kelp DSS group exhibited decreased relative abundances of Escherichia coli/Shigella and an increased molar ratio of acetic acid. In addition, kelp was observed to suppress the proliferation of the pathogenic bacteria and increase the content of volatile fatty acids in the colon of the colitis pig model (Rattigan et al, 2020). Rioux L. E., Turgeon S., and Beaulieu M. characterized the polysaccharides extracted from brown seaweeds (Rioux et al, 2010).…”
Section: Polysaccharidesmentioning
confidence: 99%